Analytical models for reverse arch and compressive arch action in horizontally restrained unbonded prestressed RC beam-column sub-assemblages. (1st February 2021) - Xu, Wenliu; Wang, Licheng
Highlights: The analytical models to predict the reverse arch action (RAA) and the compressive arch action (CAA) of unbonded prestressed RC beam column sub-assemblages under column removal scenarios were proposed. A notional eccentricity was introduced for calculating the additional bending moment of beam section. Comparisons between the experimental and FEM's results indicated that the FEM gave good predictions of CAA capacity of conventional RC beam column sub-assemblages. The effects of effective prestress, size of beam section, stiffnesses of end support restraints and span of the beam on the RAA capacity and the inverted camber can be reflected in the RAA model. The augmentation of effective prestress is advantageous to the enhancement of CAA capacity of UPRC sub-assemblage. Abstract: This paper presents the analytical models to predict the reverse arch action (RAA) and the compressive arch action (CAA) of unbonded prestressed reinforced concrete (UPRC) beam-column sub-assemblages under column removal scenarios. In the models, the realistic stress–strain model for concrete is applied to calculate the compression force sustained by concrete, instead of the equivalent rectangular concrete stress block. A linear variation of the strains for concrete and steel reinforcement along the beam length is assumed. Moreover, a notional eccentricity of eccentric force imposing on beam section is introduced in the RAA model to determine its bending moment. Comparisons between FEM's and analytical results indicate that reasonable accuracy can be obtained in predicting not only the inverted camber and the RAA capacity of the sub-assemblages by the RAA model, but also the CAA capacity and the horizontal reaction force through the CAA model. Furthermore, the effects of effective prestress on the CAA of the sub-assemblages are investigated. Finally, through a contrastive analysis, it can be concluded that the increase of effective prestress is beneficial to the enhancement of CAA capacity to mitigate structural progressive collapse but worse to the ductility of beam section.